A new species of Perymenium (Compositae-Heliantheae) from the State of Mexico (Mexico) - Rzedowski, Jerzy; Calderón de Rzedowski, Graciela (Instituto de Ecología, A.C., 2010)
Perymenium rogmacvaughii is described as new and illustrated on the basis of a specimen collected in the western extremity of the State of Mexico. The species is probably related to P. hintonii McVaugh, known from Michoacán, and to P. pringlei B.L. Rob. & Greenm. var. pringlei, reported from Jalisco and Sinaloa.